Misophonia as a Psychological Correlate of Anxiety and Depression: The Mediating Role of Obsessive-Compulsive Symptoms - Khalili Gorji , Niloufar; Karimi, Neda; Mokhtari, Tahereh; Yeganeh Srajari, Maryam; Sisiyan, Khadige (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to examine the associations between misophonia and stress, anxiety, and depression, with a specific focus on the mediating role of obsessive–compulsive symptom dimensions.Methods and Materials: This descriptive–correlational, cross-sectional study was conducted on 45 male and female clients with misophonia-related complaints who referred to counseling clinics in Tehran between July and September 2023. Participants completed the Misophonia Questionnaire (MQ), the Maudsley Obsessive–Compulsive Inventory (MOCI), and the Depression, Anxiety, and Stress Scale–21 (DASS-21). Data were analyzed using SPSS (version 27), JASP (version 0.18.1), and SmartPLS (version 4). Given the small sample size and non-normal distribution of variables, partial least squares structural equation modeling (PLS-SEM) was employed to estimate direct, indirect, and total effects. Statistical significance was set at p < 0.05.Findings: Misophonia showed significant direct associations with stress (β = 0.177, p = 0.002), depression (β = 0.252, p < 0.001), and anxiety (β = 0.203, p = 0.017). Mediation analyses indicated that obsessive–compulsive symptoms partially mediated the relationship between misophonia and stress through the checking (β = 0.181, p = 0.002) and doubting (β = 0.107, p = 0.019) dimensions. Cleaning and slowness did not demonstrate significant mediating effects (p > 0.05). No obsessive–compulsive symptom components significantly mediated the associations between misophonia and either depression or anxiety. Total effects of misophonia on stress (β = 0.390), depression (β = 0.390), and anxiety (β = 0.308) were all statistically significant (p < 0.001).Conclusion: Misophonia is significantly associated with heightened psychological distress, and specific obsessive–compulsive behaviors, particularly checking and doubting, constitute key pathways linking misophonia to stress but not to anxiety or depression.